DESIGN OF ACCOUNTING RECORDING SYSTEM AT HERI COFFEE SHOP - Budi Chandra; Charles Charles (Universitas Internasional Batam, 2022)
This PKM activity is carried out with the aim of helping one of the MSMEs in Batam in designing a financial recording system that is in accordance with the wishes of MSMEs so that it can be applied to operational activities. The partner of this activity is the Heri Coffee Shop. Kedai Kopi Heri has done the recording before, Kedai Kopi Heri tends to only record manually using a book. This makes financial records so there is no efficient. This PKM activity is carried out by means of question and answer, observation. Accounting recording system designed with Microsoft Access. The outputs obtained from this system are general ledger, trial balance, income statement, statement of financial position, inventory report. The implementation stage consists of 3 stages, namely the stage of recognizing the features of a system, submitting and receiving the system that the author designed using Microsoft Access, and feedback from the MSMEs. The system has been implemented properly and can provide revisions to the accounting record system for MSMEs.